Белковая инженерия - Корнелюк, А.И. (Біополімери і клітина, 2001)
В обзоре кратко проанализированы основные направления развития белковой инженерии – новой области молекулярной биологии и биотехнологии, базирующейся на достижениях генной инженерии, структурной биологии и компьютерных технологий. Белковая инженерия ставит задачу направленного изменения структуры белков для придания им новых или изменения существующих свойств либо создания белков de novo. Дизайн белка осуществляется на уровне его трехмерной структуры с использованием компьютерных методов моделирования. Рассмотрен метод сайт-направленного мутагенеза и его применение в белковой инженерии для структурно-функционального анализа белков. Представлены результаты структурно-функционального анализа тирозил-тРНК синтетаз бактерий и млекопитающих методами белковой инженерии. Описан дизайн искусственных белков de novo. Дана оценка перспективам развития белковой инженерии, ее использованию в биотехнологии и медицине. The main directions of protein engineering – a novel branch of molecular biology and biotechnology, – are briefly analysed in this review. Protein engineering is based on the achievements of genetic engineering, structural biology and computer technologies. The main goal of protein engineering is a directed alteration of 3D protein structure with the aim of acquisition of novel properties or change of existing properties; or protein design de novo. Protein design is carried out on the level of 3D protein structure using the computer modelling methods. The site-directed mutagenesis method and its applications in protein engineering for structural and functional analysis of proteins is considered. The results of structural and functional investigations of bacterial and mammalian tyrosyl-tRNA synthetases by protein engineering are presented. Protein design of artificial proteins de novo is described. The perspectives of development of protein engineering and its application in biotechnology and medicine are given in the review. В огляді стисло проаналізовано основні напрямки розвитку білкової інженери – нової галузі молекулярної біології і біотехнології, яка базується на досягненнях генної інженерії, структурної біології та комп'ютерних технологій. Білкова інженерія ставить своїм завданням направлену зміну струкури білків для надання їм нових чи зміни існуючих властивостей або створення білків de novo. Дизайн білка здійснюється на рівні його тривимірної структури з використанням комп'ютерних методів моделювання. Розглянуто метод сайт-спрямованого мутагенезу і його використання в білковій інженерії для структурно-функціонального аналізу білків. Представлено результати структурно-функціонального аналізу тирозил-тРНК синтетаз бактерій і ссавців методами білкової інженерії. Описано дизайн штучних білків de novo. Зроблено оцінку перспективам розвитку білкової інженерії, її використанню в біотехнології і медицині.